Systemic ozone therapy as an adjunctive treatment in guided bone regeneration: a histomorphometrical and immunohistochemical study in rats - Baggio, Ana Maira Pereira [UNESP]; Bizelli, Vinícius Ferreira [UNESP]; Delamura, Izabela Fornazari [UNESP]; Viotto, Arthur Henrique Alecio [UNESP]; Veras, Allice Santos Cruz [UNESP]; Teixeira, Giovana Rampazzo [UNESP]; Faverani, Leonardo Perez [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (Springer Nature, 2024)
Objectives: To assess the effectiveness of ozone therapy in guided bone regeneration (GBR) for critical size calvarial defects in rats. Materials and methods: 96 male Wistar rats were divided into four groups (n = 6 each). An 8 mm critical defect was created in the calvaria of each rat. The groups were: BIO (porcine collagen membrane, BioGide®), BIO + OZ (membrane with systemic ozone therapy every 2 days), COA + OZ (blood clot with ozone therapy), and COA (blood clot only). Evaluations at 7, 15, 30, and 60 days included histological, histomorphometric, inflammatory profile, Micro-CT, and immunohistochemical analyses. Statistical analysis involved two-factor ANOVA with Tukey’s post-hoc test for general data, and one-factor ANOVA with Holm-Sidak post-hoc test for Micro-CT data. Results: The BIO + OZ group demonstrated superior bone regeneration with well-organized, mature bone tissue and significant bone formation at 30 and 60 days. The COA + OZ group showed early angiogenesis and reduced inflammation, resulting in complete defect closure by 30 days. The BIO group had good regeneration, but less mature tissue compared to BIO + OZ. The COA group exhibited limited bone formation and higher porosity. Conclusion: Ozone therapy positively influences bone regeneration by enhancing cell proliferation and the healing response. Clinical relevance: Improving regenerative processes with auxiliary therapies like ozone therapy can be significant for advancing dental reconstructions.
Keywords: Biocompatible biomaterials; Bone regeneration; Inflammation; Ozone